Determinanty prawne człowieka w średniowieczu z perspektywy historycznojęzykowej = Legal determinants of man in the Middle Ages from a historical?linguistic perspective - Trawińska, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article presents preliminary findings concerning the Latin?Polish legal vocabulary found in medieval court books. On the basis of entries related to property right, it has been shown how difficult it is to determine the contextual meaning of key terms for this right, such as "hereditas" and "imienie". This is due to the nature of the records, which most often provide only brief information about the court proceedings with the details omitted.
Keywords: księgi sądowe; rękopis; średniowieczna łacina; słownictwo prawnicze; medieval court books; manuscript; Old Polish; medieval Latin; legal vocabulary